PRICE TRANSMISSION IN THE INDONESIAN RED CHILI MARKET STATIC AND DYNAMIC MODELS - Sitepu, Rasidin Karo Karo (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339)DO - 10.24843/JEKT.2022.v15.i02.p04, 2022)
The problem that often arises in agricultural commodities is the transmission of price changes at the consumer level and at the producer level. This study aims to empirically test the transmission of red chili prices using static and dynamic models. The data used is a weekly series from January 1, 2017, to November 21, 2020. The results show that the red chili price transmission is symmetrical, where price transmission between consumers - producers is perfect. The increase and decrease in the retail price of red chili will be followed by an increase and decrease in the producer price of red chili. The red chili market is a competitive market, so government intervention is not needed to control prices, but must always be monitored to maintain a perfect market mechanism. Preparation of the food balance, projections of production and demand for red chili, improvement of distribution channel infrastructure and price information systems are strategies to anticipate price fluctuations and failure of market mechanisms.